Kendala Mahasiswa dalam Mengakses Literatur Islami Digital untuk Penyusunan Karya Ilmiah: Studi Eksploratif di STAI UISU Pematangsiantar - Nur Hidayati (DIKLINKO JOURNALS PUBLISHER, 2025)
This study explores the challenges faced by students of STAI UISU Pematangsiantar in accessing Islamic digital literature for academic writing. Using a qualitative approach through interviews, observations, and document analysis, the research identifies four main categories of obstacles: accessibility, digital literacy, availability of literature, and motivation and perception. Accessibility barriers include poor internet connectivity, limited devices, and high data costs. Students’ digital literacy remains low, particularly in searching for credible sources, utilizing academic databases, and applying reference management tools. Regarding availability, relevant Islamic digital literature is still limited, while the campus repository is not yet accessible online. Although students show relatively high motivation, pragmatic perceptions and the lack of institutional support often lead them to rely on open sources with questionable credibility. The findings highlight that the students’ challenges are multidimensional, encompassing technical, financial, linguistic, and structural aspects. This study is expected to provide a foundation for strengthening Islamic digital literacy policies and facilities at STAI UISU Pematangsiantar.